Limb Position Significantly Affects Safety Distance During Cast Removal. (March 2015) - Abu-Ghanem, Yasmin; Abu-Ghanem, Nora; Albagly, Asaf; Eyal, Gil; Steinberg, Ely L.; Chechik, Ofir
<x xml:space="preserve">Abstract</x> BACKGROUND: Unintentional cast saw injuries are attributable to casting material or improper removal technique. Another factor associated with the risk of injury is the "safety distance, " the distance between the inner perimeter of the cast and the patient's skin. METHODS: Nine patients with lower leg casts around the knee/ankle were examined. Safety distance was measured using a standard depth gauge at 6–10 spots along the limb. The safety distance at each spot was measured in both supine and lateral-decubitus positions. Limb position was termed "safe" with the saw coming directly from above; a "dangerous" position was considered when the saw was coming from the side. RESULTS: The mean safety distance in the "safe position" was 17.02 mm ± 4.66 mm, compared with 14.34 mm ± 3.85 mm in the "dangerous position" (Δ = 2.7 mm; p < .0001). CONCLUSIONS: Proper positioning of a patient during cast-splitting, with the saw in the nondependent, safe aspect of the limb, can significantly increase the safety distance and minimize skin injuries.